2017
DOI: 10.19070/2332-3000-1700038
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Breakup Distress, Betrayal and Heartbreak: A Review

Abstract: Although romantic breakups, breakup distress and heartbreak are common among adults, they have occurred as early as the seventh grade [90], and most of the studies on these topics have been conducted with university students, as reflected by the literature reviewed in this paper. Romantic breakups occur in as many as twothirds of university samples [43,104]. The breakups frequently lead to breakup distress which is often associated with depression, feelings of rejection and betrayal, heartbreak symptoms includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Fisher, 2004; Gómez-López et al, 2019; Mattingly et al, 2020). Conversely, the termination of a romantic relationship has been demonstrated to trigger intense emotional turmoil (Davis et al, 2003; Field, 2017; G. W. Lewandowski et al, 2006; Preetz, 2022; Rhoades et al, 2011).…”
Section: Nonpsychotherapy Variables Affecting the Distress Of Romanti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fisher, 2004; Gómez-López et al, 2019; Mattingly et al, 2020). Conversely, the termination of a romantic relationship has been demonstrated to trigger intense emotional turmoil (Davis et al, 2003; Field, 2017; G. W. Lewandowski et al, 2006; Preetz, 2022; Rhoades et al, 2011).…”
Section: Nonpsychotherapy Variables Affecting the Distress Of Romanti...mentioning
confidence: 99%
“…Romantic relationships have been shown to play a crucial role in the psychological and emotional development across the lifespan, proving a sense of connection, fulfillment, and meaning, and contributing to identity formation and overall well-being (e.g., H. Fisher, 2004;Go ´mez-Lo ´pez et al, 2019;Mattingly et al, 2020). Conversely, the termination of a romantic relationship has been demonstrated to trigger intense emotional turmoil (Davis et al, 2003;Field, 2017; G. W. Lewandowski et al, 2006;Preetz, 2022;Rhoades et al, 2011). Several researchers have found that individuals suffering from the consequences of a breakup may be more than just sad or blue; they may experience intrusive thoughts, insomnia, anxiety, and depression, including an elevated risk of suicidal ideation (Boelen & Van den Bout, 2010;Field, 2011;Verhallen et al, 2019;Whisman et al, 2022).…”
mentioning
confidence: 99%
“…Self-help and approach coping will be studied through an exploratory approach, although it can be expected that individuals with attachment insecurities will less likely use adaptive coping strategies. All hypotheses and research questions will consider baseline levels of distress (to isolate breakup distress from general level of distress, Preetz, 2022 ) and four empirically supported potential covariates: gender (gender differences were found in post-breakup distress, Carter et al, 2018 ; Field, 2017 ; Preetz, 2022 ), breakup initiator (being the initiator has been related to lower post-breakup distress, e.g., Carter et al, 2018 ; Hunt & Chung, 2012 ), presence of betrayal (related to higher distress, Field et al, 2009 ), and involvement in a new relationship (related to lower distress, Boelen & Reijntjes, 2009 ; Carter et al, 2018 ).…”
Section: Present Studymentioning
confidence: 99%
“…Romantic breakups can affect mental health and result in various psychological symptoms, such as depressive symptoms (see Field, 2017 , for a review), including dysphoric mood and affects and the loss of motivation and interest in life ( Derogatis, 1993 ). A longitudinal study conducted by Keller et al (2007) revealed that 19.6% of the 1731 participants whose symptoms met the criteria for major depression in the last year identified that the main cause was a romantic breakup.…”
Section: Introductionmentioning
confidence: 99%
“…Grief in the context of college is an important occurrence to study because of the large impact mourning has on students' lives. Common symptoms include sleep disturbances, intrusive thoughts, feelings of depression and anxiety, changes in drug-use or eating behaviors, diminished academic performance, and endocrine and immune dysfunction (del Palacio-González et al, 2017;Field, 2013;Field et al, 2009). Although some of these symptoms are distilled from death related losses, college students often endorse similar grief symptoms when experiencing non-death related losses (Balk, 2001;Cooley et al, 2010;Gold, Miller, & Rotholz, 2001;Gold, Neururer, & Miller, 2000).…”
Section: Grief In Collegementioning
confidence: 99%